Bone marrow lesions detected by specific combination of MRI sequences are associated with severity of osteochondral degeneration. Issue 1 (December 2016) - Muratovic, Dzenita; Cicuttini, Flavia; Wluka, Anita; Findlay, David; Wang, Yuanyuan; Otto, Sophia; Taylor, David; Humphries, Julia; Lee, Yearin; Labrinidis, Agatha; Williams, Ruth; Kuliwaba, Julia
Abstract Background Bone marrow lesions (BMLs) are useful diagnostic and prognostic markers in knee osteoarthritis (OA), but what they represent at the tissue level remains unclear. The aim of this study was to provide comprehensive tissue characterization of BMLs detected using two specific MRI sequences. Methods Tibial plateaus were obtained from 60 patients (29 females, 31 males), undergoing knee arthroplasty for OA. To identify BMLs, MRI was performedex vivo using T1 and PDFS-weighted sequences. Multi-modal tissue level analyses of the osteochondral unit (OCU) were performed, including cartilage volume measurement, OARSI grading, micro-CT analysis of bone microstructure, routine histopathological assessment and quantitation of bone turnover indices. Results BMLs were detected in 74 % of tibial plateaus, the remainder comprising a No BML group. Of all BMLs, 59 % were designated BML 1 (detected only by PDFS) and 41 % were designated BML 2 (detected by both PDFS + T1). The presence of a BML was related to degeneration of the OCU, particularly within BML 2. When compared to No BML, BML 2 showed reduced cartilage volume (p = 0.008), higher OARSI scores (p = 0.004), thicker subchondral plate (p = 0.002), increased trabecular bone volume and plate-like structure (p = 0.0004), increased osteoid volume (p = 0.002) and thickness (p = 0.003), more bone marrow oedema (p = 0.03), fibrosis (p = 0.002), necrosis (p = 0.01) and fibrovascular cysts (p = 0.04). For most measures, BML 1 was intermediate between No BML and BML 2. Conclusions BMLs detected by specific MRI sequences identify different degrees of degeneration in the OCU. This suggests that MRI characteristics of BMLs may enable identification of different BML phenotypes and help target novel approaches to treatment and prevention of OA.